Synthesis of Functionalized Bicyclic Pyridones Containing the Dithiocarbamate Group Using Thioazlactones, Diamines, and Nitroketene Dithioacetal - Saeedi, Marziyeh; Khoshdoun, Maryam; Taheri, Salman; Ziyaei Halimehjani, Azim; Mohammadi, Aliasghar; Halvagar, Mohammad Reza; Amani, Vahid (SynOpen, 2021)
An efficient method for the synthesis of highly substituted bicyclic pyridone derivatives containing the dithiocarbamate group is reported via a one-pot three-component reaction of 2-(alkylthio)thioazlactones, diamines, and nitroketene dithioacetal in EtOH under catalyst-free conditions. The reaction proceeds via a domino amidation–intramolecular 1,4-addition-type Friedel–Crafts alkylation reaction to afford the corresponding fused bicyclic pyridones with high yields and diastereoselectivity.
Keywords: thioazlactone; nitroketene dithioacetal; bicyclic pyridine; dithiocarbamate; catalyst-free